Źródła finansowania miejskiego budownictwa mieszkaniowego - Denek, Emilia (Wydział Prawa i Administracji UAM, 1969)
Financing municipal housing from the budget secures adaptation of the size of financial means to the problem of the national economical plan. It is connected with non payable fulfillment of housing needs. Financing of this kind is connected with danger of reducing the size of municipal housing in the economical plan, as well as with danger of not taking into account the inhabitants' preferences in the field of standard of flats. Defects of budgetary financing can be avoided to some extend in the case of financing housing from the effective funds. Financing home building from people's own incomes subjects the supply of housing needs to the size of these incomes. It can lead to nonsupply or delay of supply of housing needs. But it is connected with taking into account the preference of the people. The advantage of credit financing of municipal housing is acceleration of supply of housing needs with taking into account the preferences of the people. Development of credit for municipal housing depends on sources of refunding the credit.
Sources of Financing of Municipal Housing